2016
DOI: 10.1097/md.0000000000005132
|View full text |Cite
|
Sign up to set email alerts
|

Sialodochitis fibrinosa (kussmaul disease) report of 3 cases and literature review

Abstract: Background:Sialodochitis fibrinosa is a rare disease which is characterized by recurring episodes of pain and swelling of the salivary glands due to the formation of mucofibrinous plugs. Analytic studies ascertain elevated levels of eosinophils and immunoglobulin E (IgE). Imaging studies such as magnetic resonance imaging (MRI) and sialography reveal dilation of the main salivary duct (duct ectasia). Treatment is initially supportive, consisting of compressive massages, and use of antihistamines and/or cortico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…Histopathology of Wharton's duct and submandibular gland tissue from the patient revealed epithelial dislodgment and the presence of a dense periductal lymphoplasmacytic infiltrate, consistent with findings in previous reports (Baer et al., 2017; Flores et al., 2016). Immunohistochemical staining revealed the presence of lymphocytes, primarily CD4 + helper T cells (Figure ).…”
Section: Figuresupporting
confidence: 91%
See 1 more Smart Citation
“…Histopathology of Wharton's duct and submandibular gland tissue from the patient revealed epithelial dislodgment and the presence of a dense periductal lymphoplasmacytic infiltrate, consistent with findings in previous reports (Baer et al., 2017; Flores et al., 2016). Immunohistochemical staining revealed the presence of lymphocytes, primarily CD4 + helper T cells (Figure ).…”
Section: Figuresupporting
confidence: 91%
“…Sialodochitis fibrinosa (also known as Kussmaul disease) was originally described by Kussmaul in 1879. This condition involves recurrent parotid grand swelling and mucus plugs containing leucocytes and Charcot–Leyden crystals (CLCs; Baer, Okuhama, Eisele, Tversky, & Gniadek, 2017; Flores et al., 2016; Ray, Burgin, & Spector, 2015). Sialodochitis fibrinosa also includes recurrent salivary gland swelling with fibrinous eosinophil‐rich mucus plugs.…”
Section: Figurementioning
confidence: 99%
“…However, sialodochitis is impossible to separate from sialadenitis clinically and the disease appears initially duct associated. The literature reported that the secretion of a fibrinous material containing numerous eosinophils from the glandular duct orifices was a distinctive finding of ES [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Few histopathological investigations into ES have been published.…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…The etiology of ES is not well understood, although the most accepted hypothesis is that it is an allergic process [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Support for an allergic etiology is based on significant medical history of asthma and chronic rhino-conjunctivitis in some patients and a raised peripheral eosinophil count in affected patients [ 9 ]. In our case, we were unable to correlate symptoms with the consumption of food allergens.…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…Although diagnostic criteria for eosinophilic sialodochitis have not been well established, specific findings commonly observed in this disease can aid its diagnosis. 3) In addition, antihistamine medication usually improves obstructive symptoms in this disease. 4) Herein, we report two cases of recurrent submandibular gland (SMG) swelling relieved by antihistamine medication, suspicious of organ-specific eosinophilic disease, with a literature review.…”
Section: Introductionmentioning
confidence: 99%